2021
DOI: 10.1101/2021.05.21.21257595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ivermectin for the treatment of COVID-19: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background: We systematically assessed benefits and harms of the use of ivermectin (IVM) in COVID-19 patients. Methods: Published and preprint randomized controlled trials (RCTs) assessing IVM effects on COVID-19 adult patients were searched until March 15, 2021 in five engines. Primary outcomes were all-cause mortality, length of stay (LOS), and adverse events (AE). Secondary outcomes included viral clearance and severe AEs. We evaluated risk of bias (RoB) using the Cochrane RoB 2.0 tool. Inverse variance ra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…The situation is worsened by confusing messages through social and traditional media plus articles from peer-reviewed journals that are published and afterwards retracted as well as the uncontrolled use of medical and veterinary products by the population ( 27 ). Meta-analyses that included studies with a variety of regimens have reached different interpretations and conclusions, preventing the achievement of consistent findings ( 14 , 18 , 28 , 29 ). In this context, a MEURI Program appears as the mean to attempt monitored and controlled use of a treatment not approved for the indication but with preliminary results of adequate safety and potential efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The situation is worsened by confusing messages through social and traditional media plus articles from peer-reviewed journals that are published and afterwards retracted as well as the uncontrolled use of medical and veterinary products by the population ( 27 ). Meta-analyses that included studies with a variety of regimens have reached different interpretations and conclusions, preventing the achievement of consistent findings ( 14 , 18 , 28 , 29 ). In this context, a MEURI Program appears as the mean to attempt monitored and controlled use of a treatment not approved for the indication but with preliminary results of adequate safety and potential efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…IVN, a well-known antiparasite medication, is considered a safe drug, and reports on its hepatotoxic effects are rare. There are growing and controversial evidences about IVN efficacy in treatment of COVID-19 patients but it seems to be a safe medication in overall (63)(64)(65)(66). Of course there is a case report of IVN caused DILI (elevated aminotransferase, acute hepatocellular necrosis, lobular infiltration of lymphocytes, and without fibrosis) 1 month after drug administration and the patient clinically improved after 3 months (67).…”
Section: Drug-induced Liver Injurymentioning
confidence: 99%
“…Another systematic review (search conducted 25 April 2021) conducted a meta-analysis of 15 RCTs measuring mortality and concluded that ivermectin compared to no ivermectin reduced the risk of death by an average of 62% ( 37 ) with the GRADE approach used to evaluate this as “moderate-certainty” evidence. Another systematic review (search conducted 22 March 2021) of 10 RCTs concluded “that ivermectin did not reduce all-cause mortality” ( 45 ). The Cochrane review (search conducted 26 May 2021) included 14 RCTs and concluded that it was uncertain whether ivermectin increased or decreased mortality and the evidence was “very low-certainty” ( 36 ).…”
Section: Systematic Reviews and Ivermectinmentioning
confidence: 99%